Comparison and quantification of estrogen receptor-mediated responsiveness to endocrine disruptors in bivalves by using complementary model and a novel yeast assay approach. (15th April 2023) - Liu, Liru; Miao, Jingjing; Liu, Peipei; Zhao, Anran; Yao, Linlin; Pan, Luqing
Abstract: Endocrine disrupting chemicals (EDCs) in estuaries and coastal habitats have been widely detected over the world and caused global concern. Bivalves have been shown to be vulnerable to endocrine disruption. However, estrogen receptors (ERs) sensitivity to steroids and EDCs has long been considered to be restricted to vertebrates. In the present study, a computational simulation docking model was applied to qualitatively predict the binding behavior of two bivalve ERs to estradiol and compared the docking activity with zebra fish ER a . A novel reconstituted yeast system was constructed by using transcriptional activator GAL-4 consists of ER-expressing plasmid and ERE (estrogen responsive element)-containing plasmid. The assays showed that bivalve ER specifically activate transcription in response to tested steroids and EDCs, but the activation ability is weaker compared to zebra fish ER a . The results corroborate the presence of an active ER in bivalve molluscs and provide a promising tool for screening of marine environmental pollutants active in disturbing ERs of bivalves, as well as understanding the underlying mechanism across taxonomic groups and phyla. Graphical abstract: Image 1 Highlights: Two key amino acid residues of bivalve ER play a role in forming hydrogen bonds with estradiol. Bivalve ERs specifically activate transcription in response to tested steroids and EDCs. The response pattern of ERs was comparable among the two bivalves and zebrafish.